2010
DOI: 10.1021/nl100058y
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Based Sequence Specific Detection of Duplex DNA for Genomic Profiling

Abstract: We demonstrate a purely electrical method for single-molecule detection of specific DNA sequences, achieved by hybridizing double-stranded DNA (dsDNA) with peptide nucleic acid (PNA) probes and electrophoretically threading the DNA through sub-5 nm silicon nitride pores. Bis-PNAs were used as the tagging probes, in order to achieve high affinity and sequence-specificity. Sequence detection is performed by reading the ion current traces of individual translocating DNA molecules, which display a characteristic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(135 citation statements)
references
References 23 publications
2
133
0
Order By: Relevance
“…These often make use of molecular adapters covalently attached to the pore and exonuclease enzymes. 13 Apparently, the interest in realizing a functional HL sequencer is still high [14][15][16] and attempts to increase the range of the HL functionality, also at alkaline pH 14 seem promising. Despite their use in a variety of studies and their manipulation to read-out DNA strands, membrane pores are sensitive to changes in the environment and can become unstable.…”
Section: Nanopore Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These often make use of molecular adapters covalently attached to the pore and exonuclease enzymes. 13 Apparently, the interest in realizing a functional HL sequencer is still high [14][15][16] and attempts to increase the range of the HL functionality, also at alkaline pH 14 seem promising. Despite their use in a variety of studies and their manipulation to read-out DNA strands, membrane pores are sensitive to changes in the environment and can become unstable.…”
Section: Nanopore Experimentsmentioning
confidence: 99%
“…This involved the hybridization of ds-DNA with peptide nucleic acid probes to discriminate between untagged and tagged DNA molecules. 16 Continuous base identification was also achieved for ss-DNA translocating through biological pores. 13 Single-base resolution implies the ability to detect the different electronic signatures of the bases.…”
Section: Read-out Protocolsmentioning
confidence: 99%
“…Solid-state nanopores are novel biosensors capable of detecting DNA molecules as they pass, one-by-one, through them. By fabricating single sub-5 nm pores (only slightly larger than the diameter of the dsDNA helix) in a 30 nm thick silicon-nitride membrane, and by tagging (invading) the duplex structure with bis-PNAs (Singer et al, 2010) they found that as The PD-loop design employing two bis-PNA probes with a standard molecular beacon enable the detection of target sequences in a highly sequence-specific manner as not one, but two PNAs are required to 'open-up' or expose the molecular beacon's target region.…”
Section: Novel Approachesmentioning
confidence: 99%
“…An innovative approach involving the introduction of highly invasive peptide nucleic acid (PNA) probes was used to label target genomes with high affinity and sequence specificity, creating local bulges (P-loops) in the molecule (figure 8c). [106] Translocation of this labeled molecule resulted in secondary DNA-PNA blockade levels, effectively barcoding a target genome. While further studies are needed to determine the ultimate spatial resolution of this technique, this methodology could potentially enable the rapid, accurate, and amplification-free identification of small 5-10 kb viral genomes including hepatitis C, dengue and West Nile virus.…”
Section: Nanopore Applications Outside Dna Sequencingmentioning
confidence: 99%